Cross-Cultural Management and Quality Performance Chinese Construction Firms in Nigeria - Babatunde, Yomi.; Low, Sui Pheng; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book explores China$1 (Bs global competitiveness in the building of infrastructures with a particular interest in the resource-rich African countries. The book begins with a comprehensive literature review on total quality management (TQM) and national culture, followed by reviews of the construction industries in China and Nigeria. This provides better understanding of the linkages between TQM, based on the International Organization for Standardization$1 (Bs ISO 9000 quality management systems (QMS), and national culture, based on Emeritus Professor Geert Hofstede$1 (Bs national cultural dimensions. Premised on the culture-specificity and bi-directionality relationships between TQM and national culture, this book investigates the construction industries in China and Nigeria including their strengths, weaknesses, opportunities, and threats (SWOT) as well as an appraisal of their historical and emerging relationships. In its conceptual approach, this book presents different models in the lead up to its primary theoretical contribution of a quality management assessment model (QMAM) that was adopted during the study$1 (Bs field work. The book also presents relevant lessons relating to cross cultural management and quality performance not only to the Nigerians but also other foreign players in Nigeria$1 (Bs construction industry.s
Introduction -- TQM and National Culture -- Construction Industry in China -- Construction Industry in Nigeria -- Relationship Between the Chinese and Nigerian Construction Industries -- Conceptual Approach -- Research Design and Method -- Results and Discussions -- Summary and Conclusions.
Keywords: Economics; Engineering; Economics/Management Science; Production/Logistics/Supply Chain Management; Construction Management; Cultural Management